DO INSTITUTIONAL AND FAMILY OWNERSHIP INFLUENCE TAX AGGRESSIVENESS? EVIDENCE FROM INDONESIAN MANUFACTURING FIRMS ON THE INDONESIAN STOCK EXCHANGE IN 2019-2023 - Putra, Mohamad Raffi Cendika; Parwati, Ni Made Suwitri; Furqan, Andi Chairil; Abdullah, M. Ikbal (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This research investigates the impact of institutional and family shareholding structures on corporate tax aggressiveness, while evaluating the role of ownership structures as a control mechanism in mitigate tax avoidance. The methodological framework is based on a quantitative approach, with multiple linear regression as the primary analytical tool for evaluating the influence of independent variables on the dependent construct in Stata 17.0. Using a purposive sampling approach, the final research dataset comprises 90 firm-year observations from 18 manufacturing entities that maintained continuous listings on the Indonesia Stock Exchange between 2019 and 2023. Tax aggressiveness is proxied by the Effective Tax Rate (ETR). The findings reveal that family ownership has no significant impact on tax aggressiveness, suggesting that family involvement in the ownership structure has yet to suppress tax avoidance effectively. Similarly, institutional ownership does not significantly influence tax aggressiveness, suggesting that institutional investors have not served as an effective monitoring mechanism for corporate fiscal policies. Theoretically, these results confirm the relevance of Agency Theory Type II in explaining the role of majority shareholders, specifically institutional and family entities, in overseeing corporate decisions to prevent tax avoidance. Practically, this study provides insights for regulators, investors, and corporate management in designing governance frameworks and ownership structures that promote tax compliance while minimizing legal and reputational risks.